Timeless standards for species delimitation - Amorim, Dalton S.; Santos, Charles Morphy D.; Krell, Frank-Thorsten; Dubois, Alain; Nihei, Silvio S.; Oliveira, Otto M.p.; Pont, Adrian; Song, Hojun; Verdade, Vanessa K.; Fachin, Diego A.; Klassa, Bruna; Lamas, Carlos José E.; et al. (Zootaxa, 2016)
Recently a new species of bombyliid fly, Marleyimyia xylocopae, was described by Marshall & Evenhuis (2015) based on two photographs taken during fieldwork in the Republic of South Africa. This species has no preserved holotype. The paper generated some buzz, especially among dipterists, because in most cases photographs taken in the field provide insufficient information for properly diagnosing and documenting species of Diptera.